ICT and Active Teaching-Learning-Assessment Process in the Engineering Education - Jadhav, Maruti R.; Kakade, Anandrao B.; Patil, M. S. (Journal of Engineering Education Transformations, 2018)
The tremendous developments in the technology in recent years have brought revolutionary changes in the education sector. The millennial learners are increasingly comfortable with technology. The change in traits and needs of the learners has been forcing education system to adapt to these learners. Information and communication Technology (ICT) plays vital role in the teaching learning activities in the engineering education such as resource creation, delivery of contents, assessment, monitoring, administration etc. In this paper such ICT tools are discussed and their analysis is done on the basis of feedbacks obtained from a group of learners. The specific activity of flipped classroom is focused with its impact on students’ participation, learning and satisfaction. The innovative numerical based assignment and its assessment using MATLAB tool are also elaborated.